Simple wire versus figure of 8 wire for sternal closure after sternotomy: a systematic review and meta-analysis - Rahayu, Devi Agustini (Journal of Indonesia Vascular Access, 2024)
Introduction: Sternotomy is associated with a range of complications, including instability, non-union, and infection, which are among the most frequent issues encountered. The standard closure method for median sternotomy involves the use of simple wires applied in either a figure-of-eight or a simple interrupted configuration. This study aims to compare the effectiveness of simple wires in a figure-of-eight pattern versus the simple wire technique for sternal closure following median sternotomy.   Methods: Data in this study were PubMed, Web of Science, Wiley, Cochrane, ProQuest, Mendeley, and ScienceDirect databases, covering the period from 2019 to 2024. This systematic review included comparative studies evaluating simple wire versus figure-of-eight techniques for sternal closure post-sternotomy. Meta-analysis was performed using Review Manager version 5.4.   Results From an initial pool of 309 articles, 6 studies were identified as eligible for analysis. These studies collectively included 8,236 patients undergoing sternal closure with the figure-of-eight technique and 2,622 patients with the simple wire technique. The meta-analysis revealed a significantly higher rate of sternal dehiscence in patients treated with the simple wire technique compared to those using the figure-of-eight technique, with an odds ratio of 0.35 (95% CI, 0.15–0.81; p = 0.01).   Conclusion: Patients undergoing sternal closure with the simple wire technique exhibited higher rates of sternal dehiscence compared to those treated with the figure-of-eight method. The figure-of-eight wire technique significantly reduced the incidence of sternal dehiscence and appears to be a more effective method for sternal closure after median sternotomy.